Meta-análise do consumo de matéria seca e das exigências nutricionais de Ovinos deslanados criados em regiões tropicais - Oliveira, Alessandra Pinto de (2016)
The objective in this study was to estimate, through mathematical models, the dry matter intake (DMI), the insoluble neutral detergent fiber intake (NDFI) and the energy and protein requirements for maintenance and gain of hair sheep raised in tropical regions. To estimate the equation parameters, a meta-analysis of 12 independent experiments of performance, comprising a total of 394 experimental units (animals) and of 7 independent experiments of nutrient requirements, comprising a total of 243 experimental units (animals) was performed. The studies were conducted in tropical conditions, using hair sheep in the growing and finishing phases and endowed of the following quantitative information: insoluble neutral detergent fiber (NDF) dietary, DMI, NDFI, body weight (BW), empty body weight (EBW), average daily gain (ADG), empty body gain (EBG), heat production (HP), metabolizable energy intake (MEI), retained energy (RE), metabolizable protein intake (MPI), and body content of crude protein of each animal was performed. The regression equations obtained were: 〖DMI〗_(((g)⁄(day)))=83.1978(±76.4551)+1.3246(±0.2775)×〖ADG〗_(((g)⁄(day)))+23.1901(±4.7486)×〖BW〗_((kg)); 〖DMI〗_((%BW))=3.0075(±0.1455)+0.004061(±0.001211)×〖ADG〗_(((g)⁄(day))); 〖DMI〗_(((g)⁄(day)))=398.83(±160.99)+27.5131(±6.6128)×〖NDF〗_((%))-0.3608(±0.07174)×〖NDF〗_((%))^2; 〖NDFI〗_(((g)⁄(day)))=-257.56(±49.9512)+22.8960(±2.4683)×〖NDF〗_((%))-0.1759(±0.02716)×〖NDF〗_((%))^2; 〖EBW〗_((kg))=-2.4852(±0.2748)+0.8821(±0.01517)×〖BW〗_((kg)); 〖EBG〗_(((kg)⁄(day)))=-0.01875(±0.004128)+0.9671(±0.02799)×〖ADG〗_(((kg)⁄(day))); For net energy for maintenance (NEm): 〖LogHP〗_(((Mcal)⁄(EBW^0.75/day)))=-1.2305(±0.07470)+2.1543(±0.3019)×〖MEI〗_(((Mcal)⁄(EBW^0.75/day))); For net energy for gain (NEg): 〖LogRE〗_(((Mcal)⁄(EBW^0.75/day)))=-0.5908(±0.05334)+0.8455(±0.04355)×〖LogEBG〗_(((kg)⁄(day))); For metabolizable protein for maintenance (MPm): 〖MPI〗_(((g)⁄(day)))=24.8470(±7.3646)+560.28(±99.6582)×〖EBG〗_(((kg)⁄(day))); For net protein for gain (NPg): 〖NPg〗_((kg⁄day))=0.1941×〖EBW〗^(-0.1058). The NDFI as a function of NDF content in the diet showed a quadratic behavior, whose point of maximum NDFI (487.50 g/day) was obtained at the level of 65.08% of NDF in the diet. The DMI as a function of NDF content in the diet also showed a quadratic behavior, whose point of maximum DMI (923.34 g/day) was obtained at the level of 38.13% of NDF in the diet. Considering an ADG of 100 g, the DMI ranged from 447.6 to 1143.3 g/day for animals with BWs ranging from 10 to 40 kg, respectively. The DMI values were, in general, lower than those reported by the NRC and AFRC systems. The requirements of NEm and metabolizable energy for maintenance were 0.059 and 0.094 Mcal/EBW0.75/day, respectively. Considering an ADG of 100 g, the NEg requirement ranged from 0.118 to 0.407 Mcal/day for animals with BWs ranging from 10 to 40 kg, respectively. The efficiencies of use of the metabolizable energy for maintenance, and gain were 0.63 and 0.36, respectively. The MPm requirement was 3.097 g/EBW0.75/day. Considering an ADG of 100 g, the NPg requirement ranged from 12.4 to 10.5 g/day for animals with BWs ranging from 10 to 40 kg, respectively. The total metabolizable energy and protein requirements values were, in general, lower than those reported by the NRC and AFRC systems. Thus, the results of this study support the hypothesis that DMI and nutrient requirements of hair sheep raised in tropical regions are lower than those reported by traditional committees nutrient requirements of sheep. Therefore, we recommend the use of the equations presented in this study for hair sheep raised in tropical regions.